2014
DOI: 10.2106/jbjs.m.00388
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Presence of Myofibroblasts in Human Elbow Capsule After Trauma

Abstract: This study presents negative results on the hypothesis that myofibroblast numbers are elevated in long-standing (more than five months) human posttraumatic elbow capsules. The absence of myofibroblasts in long-standing elbow contracture capsules is in contrast to most other studies on human tissue in the literature to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…4). In addition, human data also exhibits limited neovascularization and synovial proliferation, similar to our observations 3 . Surprisingly, similar histological results were observed for all three injury groups (Sham, Injury I and Injury II), which was unexpected since Injury I and Injury II involve direct disruption of the anterior capsule during surgery.…”
Section: Discussionsupporting
confidence: 90%
“…4). In addition, human data also exhibits limited neovascularization and synovial proliferation, similar to our observations 3 . Surprisingly, similar histological results were observed for all three injury groups (Sham, Injury I and Injury II), which was unexpected since Injury I and Injury II involve direct disruption of the anterior capsule during surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Histologically, the protocol developed in this study induced changes in the capsule tissue similar to what has been reported for biopsies taken from human patients with contracted joints. Specifically, previous studies of human tissue have reported thickened capsular tissue, disorganized dense/fibrous collagen, and increased fibroblast‐like cell proliferation, which are consistent with our findings (Table ; Fig. ).…”
Section: Disscusionsupporting
confidence: 93%
“…On blinded sections from each elbow joint, anterior capsule tissue was evaluated by a musculoskeletal pathologist using semi‐quantitative scores for several biological characteristics of interest. Analysis focused on capsule tissue because of the role of the capsule in PTJS and because we sought to compare results from this animal model to previous histological data of capsule tissue from human patients with contracted elbows . Evaluated criteria included adhesion, cellularity, inflammation, synovial proliferation and vascularity, which were scored as summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiopathogenesis remains largely unknown [3,6,7]. According to Morrey and colleagues, most of the activities of daily living can be accomplished with 100°of elbow flexion (30-130) and 100°of forearm rotation (50-50).…”
Section: Introductionmentioning
confidence: 99%